Pengaruh Kualitas dan Harga Terhadap Minat Beli Buah Melon Kotak Golden Langkawi Di UPT PATPH Sidoarjo - Nurul, Nurul; Hendrarini, Hamidah; Rizkiyah, Noor (Universitas Medan Area, 2024)
Langkawi golden box melon is a horticultural product that attracts the attention of consumers because of its uniqueness and quality. Golden Langkawi square melons have large market potential with high demand. The aim of this research is to determine the quality and price of golden Langkawi box melons at UPT PATPH Sidoarjo and influence the desire to buy this product. Consumers who have purchased boxed golden Langkawi melons at UPT PATPH Sidoarjo are the subjects of this research. Non-probability sampling is used for sampling through the purposive sampling method. This research used SEM – PLS 4.0 data analysis and involved 96 people. The results show that product quality and price have a significant influence on interest in buying boxed golden Langkawi melons at UPT PATPH Sidoarjo.